EVALUASI USABILITY SIKARSA (SISTEM INFORMASI KEARSIPAN UHNSUGRIWA) DAN ANALISIS KORELASI KOEFISIEN USABILITY DENGAN MODEL INSTRUMEN SYSTEM USABILITY SCALE - Dewa, I Dewa Gede Budiastawa; Widya Dharma Sidi; I Made Agus Oka Gunawan; Gede Indrawan (Jurnal Penjaminan Mutu, 2025)
I Gusti Bagus Sugriwa Denpasar Hindu State University is one of the Hindu State Religious Colleges which is directly under the Ministry of Religion. The many bureaucratic processes result in the production of many documents ranging from planning documents to reporting documents. In the midst of planning and reporting, there are various processes that will certainly produce various documents. The documents produced will be needed at any time, starting from the accreditation process to the accreditation institution to the audit process carried out by the inspectorate general. Ease of access to documents requires an effective and efficient archiving method, so the Uhnsugriwa Archiving Information System (SIKARSA) was developed. Since it was developed in 2021 and used effectively in 2022, this archiving information system has not been tested, especially at the level of usability, so testing is needed to determine the level of usability of the information system and provide recommendations for strategic steps in the future to maximize the function of the archiving information system. Based on the results of the analysis that has been carried out using the System Usability Scale (SUS) model and target respondents from 4 (four) types of users, namely echelon I - IV officials, non-structural officials, archivist functional officials, and other functional officials / lecturers / implementers, the results of the evaluation of the usability of the archiving information system are in the very good category with details of the category of non-structural official users of 90.75, followed by echelon I - IV officials with a value of 85.625, followed by archivist functional officials who are the main figures in archival application users of 81.25, and the category of other functional officials / lecturers / implementers with a value of 76.17, the results of the analysis show that users give values ​​in the range of 75 - 100, so that the information system is included in the appropriate and acceptable category.